Experimental investigation of Ballistic capabilities in Carbon-Kevlar composites: Effects of weight and layer variations against 9 mm projectiles - Tannachart Wantang; Manop Pipathattakul; Fasai Wiwatwongwana (Results in Materials, 2023)
The study aimed to investigate the ballistic capabilities of carbon-Kevlar composites, particularly for the design of ballistic vests against pistol bullets. carbon-Kevlar is known for its high strength, lightweight nature, and affordability, making it a popular choice in car tuning equipment. The objective was to determine the optimal number of layers and weight of carbon-Kevlar for the design of effective and safe ballistic vests. Experimental tests were conducted using carbon-Kevlar materials to evaluate their performance against FMJ 9 mm parabellum. The tests focused on measuring the penetration depth of the bullets in a ballistic gelatin block, providing insights into the required number of layers and gram per square meter (GSM) weight necessary for effective bulletproofing. Statistical analysis revealed that all factors, including the number of layers and weight, significantly influenced the penetration depth. Comparing the performance of different weights of carbon-Kevlar in stopping 9 mm parabellum projectiles, it was observed that there was a linear correlation between weight and anti-penetration performance. However, a minimum of 36 layers with a weight of 300 GSM of carbon-Kevlar was estimated to effectively stop the projectiles. These findings provided valuable guidance for the design of ballistic vests, ensuring they could effectively withstand 9 mm parabellum projectiles.